An update of laboratory diagnosis of Helicobacter pylori in the Kingdom of Saudi Arabia - Ali M Somily; Muhammad Morshed (Journal of Infection in Developing Countries)
Helicobacter pylori is a micro-aerophilic, slow-growing, Gram-negative spiral bacterium that colonizes the mucous lining of the human stomach. Infection with this bacterium has been identified as a cause of gastritis, peptic ulcer disease, and gastric mucosa-associated lymphoid tissue lymphoma. Globally, the prevalence of H. pylori-related infection is high compared to any other infectious diseases, and the rate of prevalence much higher in developing countries than in developed nations. This review article aims to describe the trend of H. pylori-related works in the Kingdom of Saudi Arabia (KSA) and the use of various laboratory tests for the diagnosis of H. pylori-related infections in adults and children. Therefore, published literature was referenced in the explanation and discussion of the different methods used to diagnose H. pylori-related disease, including papers published in the KSA and other Middle Eastern countries. The PubMed (http://www.ncbi.nlm.nih.gov/pubmed?cmd=search) search engine was used extensively. Culture and histopathology tests have been employed widely to detect this pathogen at the early stage. However, over the years, an array of tests including the rapid urease test, serology, the urea breath test, the fecal antigen test, and molecular testing have been developed to diagnose and better manage H. pylori-associated diseases since the discovery of this novel pathogen.